2008
DOI: 10.1089/sur.2008.063.supp
|View full text |Cite
|
Sign up to set email alerts
|

Early Appropriate Parenteral Antimicrobial Treatment of Complicated Skin and Soft Tissue Infections Caused by Methicillin-ResistantStaphylococcus aureus

Abstract: Background: Complicated skin and soft tissue infections (cSSTIs) are a major clinical problem, in part because of the increasing resistance of infecting bacteria to our current antibiotic therapies. Prompt appropriate treatment of infections in hospitalized patients reduces the mortality rate. Furthermore, appropriate and timely antibiotic therapy improves outcomes for cSSTIs caused by methicillin-resistant Staphylococcus aureus (MRSA). This review delineates factors to consider in the choice of initial antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…Fowler et alfound that S. aureus is more beneficial for right-sided endocarditis and bacteremia than the standard therapy; FDA approval was granted based on this study [54]. Daptomycin was reported to be effective in the treatment of skin and subcutaneous infections and blood infections caused by MRSA in many studies [12,31,35]. In the present study, 67% of MRSA strains were isolated from skin and soft tissue infections, and 12% were isolated from blood.…”
Section: Discussionmentioning
confidence: 47%
“…Fowler et alfound that S. aureus is more beneficial for right-sided endocarditis and bacteremia than the standard therapy; FDA approval was granted based on this study [54]. Daptomycin was reported to be effective in the treatment of skin and subcutaneous infections and blood infections caused by MRSA in many studies [12,31,35]. In the present study, 67% of MRSA strains were isolated from skin and soft tissue infections, and 12% were isolated from blood.…”
Section: Discussionmentioning
confidence: 47%
“…these drugs can be limited by a narrow spectrum of activity, resistance, the need for monitoring of serum concentration, and/or adverse effects [11][12][13].…”
mentioning
confidence: 99%
“…First, this study is the first to examine a newer agent with broad-spectrum activity against Gram-positive organisms (including MRSA) and demonstrated that despite the swings in antibiotic concentration that occur during CPB, antibiotic concentrations appear sufficient to kill potential pathogens. Older antibiotics (e.g., trimethoprim-sulfamethoxazole, clindamycin, and doxycycline) that generally have activity against community-associated MRSA strains are not considered reliably active against circulating health care-acquired MRSA strains (28,36). Additionally, these older antibiotics (e.g., trimethoprim-sulfamethoxazole) have not been studied in the setting of CPB, hence their pharmacokinetics and appropriateness during CPB are unknown (20).…”
Section: Discussionmentioning
confidence: 99%